Group creativity in children and adolescents - Oztop, Pinar; Gummerum, Michaela (Cognitive development, 2020)
•Social perspective coordination is a positive predictor of group creativity of children and adolescents and it mediates the relation between age and group creativity.•Intersubjectivity in groups, namely transactive dialogue and meta-communication, is not significantly related with creativity of groups.•There is a weak negative association between group creativity of children and intrinsic task motivation.•Similar to individual creativity, group creativity also progresses with development.•Collaborative story writing can be a potential alternative for understanding group creativity of children. In the landscape of continuous change and technological innovations, educational settings need constant reforms to support children acquiring the skills that are necessary for adaptation to the future. In this research we investigated one of those skills, namely the collaborative creativity of children and adolescents. The first aim of this study was to understand whether group creativity progressed from childhood to adolescence. The second aim was to assess potential mechanisms behind developmental differences in collaborative creativity. We particularly explored the role of intersubjectivity, social perspective coordination, as well as intrinsic motivation in group creativity. Fourty-eight students from primary school years 5 and 6 and Fourty-five students from secondary school years 9 and 10 formed three person groups. Group members collaboratively wrote stories that were rated by three independent subject teachers. Stories written by secondary school students were rated as more creative compared to stories of primary school students. Social perspective coordination was found as a positive predictor of group creativity. Moreover, social perspective coordination mediated the positive relation between age and group creativity. Intersubjectivity variables were not significantly related with creativity of groups. Finally, there was a weak negative association between group creativity and intrinsic task motivation. These results indicate that similar to individual creativity group creativity also progressed with development and one explanatory mechanism was the advancement in social perspective coordination.